2017
DOI: 10.1128/iai.00565-16
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pertussis and Adenylate Cyclase Toxins by Sigma Factor RpoE in Bordetella pertussis

Abstract: Bordetella pertussis is a human pathogen that can infect the respiratory tract and cause the disease known as whooping cough. B. pertussis uses pertussis toxin (PT) and adenylate cyclase toxin (ACT) to kill and modulate host cells to allow the pathogen to survive and persist. B. pertussis encodes many uncharacterized transcription factors, and very little is known about their functions. RpoE is a sigma factor which, in other bacteria, responds to oxidative, heat, and other environmental stresses. RseA is a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…FhaB is an adhesin that allows B. pertussis to adhere to the airway during infection. In previous experiments we observed that fhaB is one of the most abundant transcripts in the transcriptome (10). We also detected both pertussis and adenylate cyclase toxin transcripts in the infected lung tissue (Table 2).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…FhaB is an adhesin that allows B. pertussis to adhere to the airway during infection. In previous experiments we observed that fhaB is one of the most abundant transcripts in the transcriptome (10). We also detected both pertussis and adenylate cyclase toxin transcripts in the infected lung tissue (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Overall, all of the samples were observed to have similar RIN numbers. For comparison with in vitro grown B. pertussis , we used samples from SSM in vitro grown UT25 extracted and analyzed by RNAseq using an identical procedure previously published by our laboratory (10). These In vitro grown B. pertussis UT25 RNA samples had RIN numbers of 9–10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. pertussis stress responses are poorly understood. Recent work showed altered virulence factor secretion following induction of the two-component stress response operon Rpo/Rse, with increased secretion of ACT and decreased production of PT (49). Our future work will seek to determine the nature of the PGLYRP4-TCT interaction, whether PGLYRP4 also mediates its anti-inflammatory activity through effects on other virulence factors, whether PGLYRP4 induces B. pertussis stress responses or direct bacterial killing, and the impact of these responses on infection.…”
Section: Discussionmentioning
confidence: 96%
“…We now know that there are other pathways by which virulence is controlled in this genus (57)(58)(59)(60)(61), but how these pathways relate to one another and to Bvg is still to be fully determined. The Bvg system controls production of many bacterial proteins-importantly ACT and other virulence factorsand expression is downregulated in response to sulfate, nicotinic acid, and a shift to lower temperature (25°C).…”
Section: Discussionmentioning
confidence: 99%